2018
DOI: 10.1371/journal.pgen.1007173
|View full text |Cite
|
Sign up to set email alerts
|

Glass promotes the differentiation of neuronal and non-neuronal cell types in the Drosophila eye

Abstract: Transcriptional regulators can specify different cell types from a pool of equivalent progenitors by activating distinct developmental programs. The Glass transcription factor is expressed in all progenitors in the developing Drosophila eye, and is maintained in both neuronal and non-neuronal cell types. Glass is required for neuronal progenitors to differentiate as photoreceptors, but its role in non-neuronal cone and pigment cells is unknown. To determine whether Glass activity is limited to neuronal lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 100 publications
(146 reference statements)
0
17
0
Order By: Relevance
“…PIP82 is not required for specification of photoreceptors but rather is a terminal differentiation gene. Moreover, we demonstrate that PIP82 transcription is regulated by the known transcriptional drivers of photoreceptor differentiation Glass and Pph13 [25][26][27][28] and, functionally, that the loss of PIP82 impacts the morphological differentiation and maintenance of rhabdomere structure. We further show that PIP82 is a post-translational target of aPKC and phosphorylation of PIP82 regulates cortical membrane localization of the protein.…”
Section: Plos Geneticsmentioning
confidence: 80%
“…PIP82 is not required for specification of photoreceptors but rather is a terminal differentiation gene. Moreover, we demonstrate that PIP82 transcription is regulated by the known transcriptional drivers of photoreceptor differentiation Glass and Pph13 [25][26][27][28] and, functionally, that the loss of PIP82 impacts the morphological differentiation and maintenance of rhabdomere structure. We further show that PIP82 is a post-translational target of aPKC and phosphorylation of PIP82 regulates cortical membrane localization of the protein.…”
Section: Plos Geneticsmentioning
confidence: 80%
“…Glass plays a fundamental role for the differentiation of rhabdomeric PRs in the fruit fly [9, 11, 45, 46]. To investigate if it provides a similar function across metazoans, we first decided to search for Glass homologues in other species.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, intron-retaining mRNA transcripts can remain in the nucleus and be spliced upon requirement providing a source of transcript that could be faster activated than by de novo transcription [26]. Recent RNAseq data suggests that intron 4 is not retained in the glass mRNA [4]. The authors found that expression of either the glass RA+RC or the glass RB transcript from transgenic constructs resulted in production of functional Glass protein, suggesting that in their ectopic expression experiments, intron 4 of the RB transcript was spliced out to produce full-length Glass PA (and PC) protein.…”
Section: Discussionmentioning
confidence: 99%
“…The zinc-finger transcription factor Glass provides a critical link betwee the RDN and terminal differentiaton. Glass is required during eye development for the differentiation of photoreceptor neurons, patterning of the ommatidia, as well as for the differentiation of cone- and pigment-cells [1-4]. glass mutants were first discovered by H.J.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation